Edible Garden Tower: Solusi Optimalisasi Lahan Pekarangan dan Peningkatan Kemandirian Pangan di Desa Slogoretno, Wonogiri - Nazalti, Zulfa; Komala, Lintang Afifatz; Almira, Andrea Keysha; Febyan, Ardelia Rahma; Athallah, Muhammad Eishaf; Dewi, Reisha Karina; Candra, Daniel Ritchie; Wirawan, Bima; M. Shohibuddin (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
The majority of the residents of Slogoretno Village have large yards that are not being used optimally. The Edible Garden Tower can be a solution to maximize the use of residents' yards in Slogoretno Village for productive agriculture. This activity aims to provide comprehensive training on the application of the Edible Garden Tower to the community. The Edible Garden Tower training activity is conducted through interactive socialization and practice. The method used is a pre-test and post-test analyzed through frequency distribution to measure the program's effectiveness. The economic aspects of implementing the Edible Garden Tower are analyzed through economic profit projections. The results of the Edible Garden Tower implementation show improvements in cognitive (87.5%), affective (100%), and psychomotor (100%) domains. Economic projections indicate commercial profits from the implementation of the Edible Garden Tower ranging from Rp1.140.480 to Rp3.024.000. The Edible Garden Tower training program is effectively implemented among the community to enhance land productivity and food self-reliance. The long-term implementation of the Edible Garden Tower provides economic benefits both subsistence and commercial.